In Vivo Bacteriophages’ Application for the Prevention and Therapy of Aquaculture Animals–Chosen Aspects - Patrycja Schulz; Joanna Pajdak-Czaus; Andrzej Krzysztof Siwicki (Animals, 2022)
To meet the nutritional requirements of our growing population, animal production must double by 2050, and due to the exhaustion of environmental capacity, any growth will have to come from aquaculture. Aquaculture is currently undergoing a dynamic development, but the intensification of production increases the risk of bacterial diseases. In recent years, there has been a drastic development in the resistance of pathogenic bacteria to antibiotics and chemotherapeutic agents approved for use, which has also taken place in aquaculture. Consequently, animal mortality and economic losses in livestock have increased. The use of drugs in closed systems is an additional challenge as it can damage biological filters. For this reason, there has been a growing interest in natural methods of combating pathogens. One of the methods is the use of bacteriophages both for prophylactic purposes and therapy. This work summarizes the diverse results of the in vivo application of bacteriophages for the prevention and control of bacterial pathogens in aquatic animals to provide a reference for further research on bacteriophages in aquaculture and to compare major achievements in the field.